Ibn Sina’s Political Philosophy: A Study of the Relationship between Prophecy and Civil Science - Bani Yasin, Derar Ali (Jordan Journal of Social Sciences, 2023)
This study examined civil science (politics) among philosophers of Islam, drawing on the theoretical ideas and approaches of Ibn Sina in his political philosophy and aimed at justifying his own vision on the nature of the conditions required in the body of a virtuous civil society. The study concluded that in his political thinking, Ibn Sina dealt with the model of the Islamic Arab State, and largly moved away from emulating the Greek political influence. The results showed that Ibn Sina tried to present an Islamic political theory closer to reality, but through the rationality of this reality he thought that the righteousness of civil assembly and the regularity of people remained conditional on prophecy and sharia law. Thus, he didn’t imagine the realization of a virtuous city apart from the existence of prophecy.